(untitled) (Research, Society and Development, 2022)
Objective: Describe the epidemiological profile of women diagnosed with gestational syphilis in Minas Gerais and Brazil between the years 2014 and 2018. Methodology: Descriptive epidemiological study regarding the cases of syphilis in pregnant women reported on the website of the Department of Informatics of the SUS. The variables collected were sociodemographic data, the geographical distribution of cases, treponemal and nontreponemal tests, and clinical classification. The data were tabulated and treated quantitatively and subjected to descriptive analysis. Results: In Brazil, 220,941 cases of syphilis in pregnant women were reported between the years 2014 and 2018, with 7.35% in Minas Gerais, showing a high incidence rate. Regarding age group and education, the highest frequency is in women between 20 and 39 years old, with 19.8 % presenting incomplete 5th to 8th grades of elementary school. Testing increased, especially in the Southeastern Region, with Minas Gerais occupying the third national position, representing 5.35% of reactive treponemal tests and 7.79% of reactive nontreponemal tests. The prevalent clinical classification was primary syphilis in pregnant women aged 15 to 59 years. A notable number of ignored/white cases occurred in the analyzed variables, which corresponds to a high underreporting regarding gestational syphilis. Conclusion: The results point to an increase in the number of gestational syphilis cases in Brazil and Minas Gerais, evidencing the need for investment in expanding access to health information for women.